Formation pressure distribution and productivity prediction of fractured horizontal wells in stress sensitive reservoirs - Huzhen, Wang; Tiancheng, Liu; Zhuangzhuang, Sun; Chunyao, Wang; Zhenyu, Liu; Zhijun, Zhou; Changjun, Diao; Zhiming, Zhao (Frontiers in Energy Research, 2022)
Aiming at the problems of formation pressure distribution and productivity prediction after Horizontal Well Volume Fracturing in stress sensitive reservoirs, the methods of dynamic permeability and dynamic threshold pressure gradient are used to deal with the influence of stress sensitivity, a numerical simulation method of oil-water two-phase flow based on finite element method is established. History matching is performed on the basis of the prediction of formation pressure distribution after horizontal well volume fracturing of, which ensures high matching accuracy. Taking the ultra-low permeability sandy glutenite reservoir of Baikouquan Formation in M18 area of Aihu Oilfield as research object, the influence law of formation pressure level on productivity and stress sensitivity on formation pressure distribution is studied. Analysis of the calculation results shows that: the influence of formation pressure level on well productivity is mainly in the first year of production, and the effect of energy increasing by volume fracturing is clarified. Stress sensitivity mainly affects the middle and later stage of production. With the increase of sensitivity, the permeability loss of the formation tends to be concentrated in the low-pressure area near the artificial fracture, forming an isolation zone with high flow resistance, which make the development effect of far well zone worse.